If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 3b + 25 Reorder the terms: 13 = 25 + 3b Solving 13 = 25 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 13 + -3b = 25 + 3b + -3b Combine like terms: 3b + -3b = 0 13 + -3b = 25 + 0 13 + -3b = 25 Add '-13' to each side of the equation. 13 + -13 + -3b = 25 + -13 Combine like terms: 13 + -13 = 0 0 + -3b = 25 + -13 -3b = 25 + -13 Combine like terms: 25 + -13 = 12 -3b = 12 Divide each side by '-3'. b = -4 Simplifying b = -4
| 17x+x=180 | | 9+6r=69 | | =(7b^2+2b-5)-(3b^2+2b-6) | | 14-5x-15=8x+13-6x | | 2x+72=5x | | 7xy+9xy=96whatisy | | 80=100-9.1(x-1.9) | | 4g+7=-5g-1+g | | 0.8=100-9.1(x-1.9) | | =(-2p^3-5p+7)+(-4p^2+8p+2) | | 5+3k=-16 | | 10000=x-3000 | | 10000a=2x-3000 | | -7(6+7p)+7(8p+3)=-35 | | -3x-8=-8+3x | | -6(3-6k)+2(8-5k)=-54 | | 3x(4x+9)= | | -120=6(-6-7x) | | -3x^2-22x-7=0 | | -6x^2+5x+21=0 | | -88=-4(-6+7v) | | -4x^2-2x+56=0 | | -3(-4a-5)+6a=105 | | 44=6x-12y | | 44=6x-12 | | 6x-12y=44 | | -2x^2-22x-48=0 | | -3x^2-20x-32=0 | | 2y=6x+10 | | -6x^2-12x+48=0 | | -192=-8(1-3x)+8 | | 3x-1=x+2 |